Prevalence and distribution of oral health knowledge according to sociodemographic, behavioural and clinical characteristics in selected coastal districts of Tanzania - Minja, Irene K.; Astrom, Anne N.; Masalu, Joyce R. (Tanzania Journal of Health Research, 2016)
Background: Having knowledge about health issues is necessary for making informed decisions related to practicing lifestyles conducive to good health. The aim of this study was to identify socio-demographic, behavioural and clinical covariates of knowledge related to the cause and prevention of oral diseases among older adults in Tanzania. Methods: A cross sectional household survey was conducted in two regions of Tanzania; Pwani and Dar es Salaam city. A total 1031 older adults aged 55 and above were personally interviewed, before undergoing a full mouth examination. Results: the proportion of older adults with knowledge (total knowledge score≥ 1) on dental caries and gum disease was 14.9% and 2.3%, respectively. Having low education level, belonging to a lower wealth quartile and lack of perceived need to see a dentist, were strongly associated with having no knowledge on dental caries. None of the covariates were significantly associated with knowledge on gum disease. Conclusion: Knowledge on the two oral diseases is low among older adults interviewed. Factors associated with knowledge demonstrate substantial socio economic disparities. Development of policies and health education programs that target behavioural and socio economic determinants is recommended.